Rethinking violence against women (SAGE series on violence against women)
Based on workshops sponsored by the Harry Frank Guggenheim Foundation, recurrent themes in this study of violence against women include: authority, women as sexual property, the assymetry of women, socialisation, patterns and deviations of victims and offenders, personal accounts and socio-cultural contexts